HYDROALLANTOIS IN A JAFARABADI BUFFALO: A CASE REPORT - Dhami, MA; Dhami, AJ (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Hydroallantois or dropsy of allantois is a sporadic pathological condition of dairy cattle and buffaloes affecting late gestation. It accounts for about 80-90 per cent of uterine hydrops and is characterized by a rapid and excessive accumulation of watery, amber coloured fluid inside the allantoic cavity over a period of 5 to 20 days giving suspicion for twin/multiple pregnancy (Sloss and Dufty, 1980; Morrow, 1986; Selvaraju et al., 2012). This condition invariably results in fetal gestational accident owing to placental dysfunction and fetal kidney failure (Arthur et al., 1996; Jana and Ghosh, 2012). Roberts (1986) stated that this dropsical condition usually affects both fetus and fetal membranes. Perusal of literature revealed that the reports on hydroallantois in buffaloes and its timely management are meager (Chandolia et al., 1989; Chaudhary and Chaudhary, 2005; Manokaran et al., 2011; Selvaraju et al., 2012). Hence this report is placed on record of a rare case of hydroallantois in a Jafarabadi buffalo with authors’ serious concern about timely management of such cases to sustain the life at least of the affected dam.